High Luminous Efficacy Phosphor-Converted Mass-Produced White LEDs Achieved by AlN Prebuffer and Transitional-Refraction-Index Patterned Sapphire Substrate - Shuo Zhang; Meng Liang; Yan Yan; Jinpeng Huang; Yan Li; Tao Feng; Xueliang Zhu; Zhicong Li; Chenke Xu; Junxi Wang; Jinmin Li; Zhiqiang Liu; et al. (Nanomaterials, 2022)
Constant advance in improving the luminous efficacy (ηL) of nitride-based light-emitting diodes (LEDs) plays a critical role for saving measurable amounts of energy. Further development is motivated to approach the efficiency limit for this material system while reducing the costs. In this work, strategies of using thin AlN prebuffer and transitional-refraction-index patterned sapphire substrate (TPSS) were proposed, which pushed up the efficiency of white LEDs (WLEDs). The AlN prebuffer was obtained through physical vapor deposition (PVD) method and TPSS was fabricated by dry-etched periodic silica arrays covered on sapphire. Devices in mass production confirmed that PVD AlN prebuffer was able to improve the light output power (φe) of blue LEDs (BLEDs) by 2.53% while increasing the productivity by ~8% through shortening the growth time. Additionally, BLEDs on TPSS exhibited an enhanced top ηext of 5.65% in contrast to BLEDs on the conventional PSS through Monte Carlo ray-tracing simulation. Consequently, φe of BLEDs was experimentally enhanced by 10% at an injected current density (Jin) of 40 A/cm2. A peak ηL of 295.2 lm/W at a Jin of 0.9 A/cm2 and the representative ηL of 282.4 lm/W at a Jin of 5.6 A/cm2 for phosphor-converted WLEDs were achieved at a correlated color temperature of 4592 K.